Influence of Leadership, Loyalty, and Followership on Team Performance of P.T. Gaharu Galangan International - Endang Tri Pujiastuti; Hasri Nirmala Budiarti; Karina A. Sulaeman; Danny Faturachman; Rini Setiawati (International Journal of Marine Engineering Innovation and Research, 2020)
Many factors are deemed influencing team or group performance. This research identifies influence of variables of leadership, followership and loyalty on team performance.  This research is quantitative research on path analysis by using SPSS program. The result is loyalty and followers don’t have direct positive effect on team performance, but through leadership variable as intervening variable. Leadership variable has direct positive effect on team performance and loyalty, and followership variable has direct positive effect on leadership variable.